1999
DOI: 10.1080/02626669909492266
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall distribution function for Libya and rainfall prediction

Abstract: Monthly rainfall amounts are distributed according to different frequency distribution functions in different parts of the world. However, in extremely arid regions gamma probability distribution functions are most often found to fit the existing data well. Libyan monthly rainfall distributions are found to abide by gamma probability distribution function which is confirmed on the basis of chi-square tests. Almost all the rainfall sequences recorded for at least the last 20 years in Libya are investigated stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The difference between the coldest and hottest mean monthly temperatures ranges from ~10-18°C, varying across the region with altitude (Ageena et al, 2014). The wettest months occur between December and February, when monthly total precipitation can exceed 100 mm (Şen and Eljadid, 1999;. Rainfall events between May and September are extremely rare.…”
Section: Study Area: the Gebel Akhdarmentioning
confidence: 99%
“…The difference between the coldest and hottest mean monthly temperatures ranges from ~10-18°C, varying across the region with altitude (Ageena et al, 2014). The wettest months occur between December and February, when monthly total precipitation can exceed 100 mm (Şen and Eljadid, 1999;. Rainfall events between May and September are extremely rare.…”
Section: Study Area: the Gebel Akhdarmentioning
confidence: 99%
“…Now, taking the specification of an FSO transceiver that is specified for 2km, and another one specified for 0.8km distance with the following data and assumptions (worst case assumptions) [8]: Using all the data recorded in the (LNMC) of the rainfall rate through about 60 years to find the resulted ranges (in km) and wither or not Rain affects the FSO performance in Libya [2] and [9]. The seasonal percentage of precipitations of rainfall in the above mentioned 60 years in fourteen Libyan cities are listed in Table I.…”
Section: Fso Equation and The Empirical Rain Attenuation Modelmentioning
confidence: 99%
“…In Libya, the weather throughout the years has not been snowy or foggy except for some regions in the mountains. Here, in this paper a modified rain equation along with the data measured and recorded in the Libyan National Meteorological Center (LNMC) are used in the analysis and simulation of the FSO link and only the rain effect is considered [2].…”
Section: Introductionmentioning
confidence: 99%
“…Olofintoye et al [12] showed that for peak daily rainfall in Nigeria, 50% of stations follow LP3 distributions and 40% follow Pearson type 3 (P3) distributions. Sen et al [13] found that the gamma probability distribution provided the best fit to monthly maxima rainfall in arid regions in Libya. Arora & Singh [14] found that the LP3 distribution recommended by the U.S. Water Resources Council (USWRC) in 1967 was the best method of flood frequency analysis in the United States.…”
Section: Introductionmentioning
confidence: 99%